The bioleaching potential of a bacterial consortium. (October 2016) - Latorre, Mauricio; Cortés, María Paz; Travisany, Dante; Di Genova, Alex; Budinich, Marko; Reyes-Jara, Angélica; Hödar, Christian; González, Mauricio; Parada, Pilar; Bobadilla-Fazzini, Roberto A.; Cambiazo, Verónica; Maass, Alejandro
Highlights: A consortium of five bacteria involved in copper bioleaching was sequenced. A model of metabolic pathways representing the bioleaching was constructed. The consortium showed a high capacity to resist heavy metals. This is the first operational industrial bioleaching consortium described to date. Abstract: This work presents the molecular foundation of a consortium of five efficient bacteria strains isolated from copper mines currently used in state of the art industrial-scale biotechnology. The strains Acidithiobacillus thiooxidans Licanantay, Acidiphilium multivorum Yenapatur, Leptospirillum ferriphilum Pañiwe, Acidithiobacillus ferrooxidans Wenelen and Sulfobacillus thermosulfidooxidans Cutipay were selected for genome sequencing based on metal tolerance, oxidation activity and bioleaching of copper efficiency. An integrated model of metabolic pathways representing the bioleaching capability of this consortium was generated. Results revealed that greater efficiency in copper recovery may be explained by the higher functional potential of L. ferriphilum Pañiwe and At. thiooxidans Licanantay to oxidize iron and reduced inorganic sulfur compounds. The consortium had a greater capacity to resist copper, arsenic and chloride ion compared to previously described biomining strains. Specialization and particular components in these bacteria provided the consortium a greater ability to bioleach copper sulfide ores.